A Study on Socio-economic Profile of the Broiler Farmers in Mizoram - Sailo, Lalruatfela; Das, Samares Kumar (International Journal of Bio-resource and Stress Management, 2018)
Transformed from backyard rearing to commercially organized industry in last five decades, India is the second largest egg producer and third largest broiler-chicken producer in the world. Mizo people traditionally rear poultry in the backyard. Poultry production in Mizoram took turn in the late eighties with establishment of broiler farms in the state. Though there is no large scale poultry farm in Mizoram, almost 70 percent of the farmers keep poultry for subsidiary income. Though studies were abundant in other states of India, studies on broiler farming are rare in Mizoram. Keeping this in view, a research was undertaken to study the socio-economic profile of the broiler farmers to help R&D professionals to improve the situations. Two districts, Aizawl and Kolasib, were selected purposively for the based on the number of broiler farms. From each district, two development blocks and from each block five villages were selected purposively based on the number of broiler farms. Total 20 villages were selected.From each village five farmers engaged in broiler farming were selected randomly. So, the total number of respondents for the study was 100, i.e. 50 from each district. A pre-tested semi-structured interview schedule was used for data collection. The data were compiled, tabulated and analyzed using percentage, frequency and chi-square test. Results revealed that majority of the farmers were middle-aged male with middle school education living in nuclear medium size family rearing a flock of 100-1,000 birds. They always used television and newspaper. A study on extension education service need assessment of the broiler farmers is recommended.